Pentingnya Kesadaran Hukum Masyarakat untuk Meningkatkan Daya Saing Usaha Mikro, Kecil dan Menengah (UMKM) di Era Digital pada Kelurahan Sembulang Kecamatan Rempang Pulau Galang Kota Batam - Christiani Prasetiasari; Nicha Suwalla; Irpan Husein Lubis; Annisa Rizky Andrini; Annisa Delviane; Citra Permata Sitohang; Tania Puji Andriani; Markis Markis; Istighfari Istighfari; Fernando Lumban Gaol (Penerbit Goodwood, 2023)
Purpose: This study discusses the importance of public legal awareness to increase the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the digital era in Sembulang Village, Rempang District, Galang Island, Batam City. Methodology: Through a normative juridical approach, this study analyzes regulations and legal norms related to MSMEs. Using regulatory, historical, and comparative approaches, this study identifies the important role of these regulations in facilitating the growth of MSMEs in the digital era. Result: The results show that the Indonesian government has taken diverse and comprehensive actions to support the growth of Micro, Small and Medium Enterprises (MSMEs) in the digital era. Through digital infrastructure policies, tax incentives, personal data protection, regulatory simplification, cooperation with technology companies, access to digital financing, and digital training, the government seeks to create a conducive environment for MSMEs to innovate and compete in the digital economy. With an inclusive approach and strong support, MSMEs have a greater opportunity to utilize digital technology, expand market reach, and contribute significantly to Indonesia's economic growth in this digital era. A deep understanding of the types of standard certificates.